THE FEMALE IN THE PAGAN (PRE- ISLAMIC)POETRY A READING IN THE MARKS OF BEAUTINESS AND CHERISHING - Dr. Mushtaq Taleb Muneam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research tackles one of the most important objects which the poets talked a lot about itin their collections of poems through many ages. Their stories had been endless with the female they wrote many poems about her. They had flown in their imagination in the wide space, imagining the most precise details about the female. Since beauty and cherishing are the brands of the female, hence it was important to study it. It is worth to mention that thepoets were differ in the using of beautiness and cherishing, from each one to another, this because of the difference in thee point of views and the varied sense, as well as the differences in cultures. Thus as a result of this, the poetry production where not similar to each other. In addition, the culture of that age had produced a special mark for beautiness and cherishing, and it were divided into two divisions, the first one is the physical beautiness and the second one isthe spiritual and ethical beautiness. Each division includes marks which considered as privileges of that division. The cherishing marks had been divided into tow parts, the first the first one is the tangible cherishing and the second one is the spiritual cherishing. Sometime there had been interference between the marks of the beautiness and the marks of cherishing. This research is the first try to discover the characteristics of beautiness and cherishing, which were the features of the females in the pagan (Pre-Islamic) age, this study comes from a masculinity point of view that express what it see in the other ( the female), what kind of beautinessmarksthat make it in an admiration level and a unique attention. It seems that the female had been knowing its important role in her society at that time; althoughlooking at her as she is a weaker than the man.